Official communications of the European External Action Service with Russia: Crafting the image of normative power Europe - Lyudmila Igumnova (Europa-Kolleg Hamburg, Institute for European Integration, 2018)
The paper explores Russia-related official statements and press releases of the European External Action Service (EEAS), as well as speeches of the European Union's two High Representatives for Foreign Affairs and Security Policy posted on the website of the service in the period of 2010-2017. The goal of the analysis is to distinguish the elements of normative, soft and transformative power in the EU's official communications with Moscow and to specify what type of power and influence the EU tries to exercise in Russia. Quantitative text analysis of the EEAS documents was carried out for this purpose. The results obtained demonstrate that the EEAS communications towards Russia are limited to a narrow range of problems; the principles of the rule of law, human rights and fundamental freedoms dominate in its dialogue with Moscow. Criticizing mainly violations of legal norms, the European External Action Service positions itself as a normative actor, promoting a normative agenda in the country. The elements of soft and transformative power are very scarcely represented. The problem of the EU's normative impact is beyond the scope of this paper.
Keywords: 320; European Union; Russia; European External Action Service; Russia-EU relations; Normative Power